PELAKSANAAN EKSTRAKURIKULER PADUAN SUARA DI SMPN 8 PAYAKUMBUH - Dilla Chotma Aldra; Esy Maestro; Yensharti Yensharti (FBS Universitas Negeri Padang, 2014)
Abstract This study aims to describe the implementaton of extracurricular choir in SMPN 8 Payakumbuh. This type of research is descriptive qualitative. Techniques of data collection by observation, interview and documentation. Research instrument is the author’s own self with the help of tools such as field data, recording interview and observation notes photo camera. Implimentation extracurricular choir at SMPN 8 Payakumbuh has been started from the year 2009 till now. Problem arising from the implementaton of that in term of infrastructure management and coaching partcipants. Studen interest is also one of the major problems in the implementation of this extracurricular choir. Inhibiting factor in extracurricular choir is less than the maximun student, attendance lack of motivation from parets, accuracy of tone, articulaton pronunciation song, and its impact on each other in the singing voice of students between one and two voice. Extracurricular activities while supporting factor is very strong support from the school and a strong willngness of coaches. Kata kunci: Extracurricular, choir, implementation,inhibiting and supporting factors.